What Makes an Agency Independent?. Issue 4 (29th January 2015) - Selin, Jennifer L.
<x xml:space="preserve">Abstract</x> The responsiveness of government agencies to elected officials is a central question in democratic governance. A key source of variation in responsiveness is agency structure. Yet scholars often view agencies as falling into broad structural categories (e.g., cabinet departments or independent commissions) or fixate on some features of design (e.g., "for cause" protections). I develop new estimates of structural independence based on new data on 50 different structural features of 321 federal agencies in the federal executive establishment. Using a Bayesian latent variable model, I estimate independence on two dimensions: limits on the appointment of key agency decision makers and limits on political review of agency policy. I illustrate the value of this new measure by using it to examine how structure affects political influence and how agency independence can vary over time.